Governance of quality of life and well-being subjective - Cruz (Adversia, 2019)
This work was proposed to establish a correlative model to discuss the importance of other variables in the investigation of the quality of life. Once the relationships between the factors derived from the literature review were specified, it conducted a cross sectional study with a non - probabilistic sample of 245 students. When the validity and reliability of the instrument measured was obtained: life satisfaction, expected capabilities, expectations of opportunity, trust relationships, perception of justice, assessment of the environment, standards of context and perceived resources, a structural model was tested in which the perceived availability of resources indirectly correlated to life satisfaction through standards context. The results were compared with findings reported in the state of knowledge.